Interaction Of Macrozoobenthos Abudance With Environmental Conditions In Segara Anakan, Cilacap - Kresnasari, Dewi; Ayu, Nurina; Gitarama, Arbi Mei (Universitas Malikussaleh, 2022)
Segara Anakan Lagoon is a unique and distinctive area where most of the ecosystem is dominated by mangrove ecosystems. Some fauna make the ecosystem as a place for feeding ground, nursery ground and spawning ground for example macrozoobenthos. Its sessile nature makes the biota used as a bioindicator of an area. The Segara Anakan mangrove forest is currently under pressure due to the process of sedimentation and conversion of functions by residents. Therefore, this study aims to determine the interaction between the abundance of macrozoobenthos with environmental conditions. The research was carried out in July-September 2021 at the Segara Anakan Lagoon, Cilacap. The sampling method used is the Sample Survey Method with three stations determined purposively by describing different habitat conditions. Sampling was carried out on a monthly and the data obtained were analyzed by PCA. The results showed that the highest abundance of macrobenthos was found in the western part of the Segara Anakan mangrove forest. The value of macrozoobenthos abundance is influenced by TSS related to food availability. Furthermore, the quality of water and soil is still in accordance with the quality standards of marine life.Keywords: Environmental Characteristics; Macrozoobenthos; Mangrove; Segara Anakan